Bis(2-methyl-1H-indole-3-carbaldehyde 4-hydroxy-benzoylhydrazonato-kappa N-2,O)nickel(II) N,N-dimethylformamide disolvate dihydrate - Ali, Hapipah Mohd; Ng, S.W.; Xie, M.J.; Najwa, M.I. (International Union of Crystallography, 2006)
The title compound, [ Ni( C17H14N3O2)(2)] center dot 2C(3)H(7)NO center dot 2H(2)O, contains Ni-II cations ( site symmetry 1) chelated by two deprotonated Schiff bases in a trans-NiN2O2 square-planar geometry. The complex molecule and the dimethylformamide ( DMF) and water molecules interact by way of O-(HO)-O-... and N-(HO)-O-... hydrogen bonds, resulting in a layered structure.